Tunable porosity in bimetallic core-shell structured palladium-platinum nanoparticles for electrocatalysts. (1st January 2019) - Shim, Kyubin; Lin, Jianjian; Park, Min-Sik; Shahabuddin, Mohammed; Yamauchi, Yusuke; Hossain, Md Shahriar A.; Kim, Jung Ho
Abstract: A porous bimetallic palladium-platinum (Pd@Pt) nanoparticles (NPs) are prepared by using two different surfactants, poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (Pluronic® F-127) and polyethylene glycol hexadecyl ether (Brij® 58). Using the Pluronic® F-127 results in a more porous structure and a larger electrochemically active surface area, even though the sizes of the Pd@Pt NPs prepared using the two different surfactants are similar, approximately 100 nm. It is revealed that the Pluronic® F-127 surfactant can introduce more electrochemically active sites into the Pd@Pt NPs nanoparticles, results in enhanced bisphenol A detection with better sensitivity. Graphical abstract: Unlabelled Image